2015
DOI: 10.1002/mgg3.143
|View full text |Cite
|
Sign up to set email alerts
|

Critical roles for WDR72 in calcium transport and matrix protein removal during enamel maturation

Abstract: Defects in WDR72 (WD repeat-containing protein 72) cause autosomal recessive hypomaturation amelogenesis imperfecta. We generated and characterized Wdr72-knockout/lacZ-knockin mice to investigate the role of WDR72 in enamel formation. In all analyses, enamel formed by Wdr72 heterozygous mice was indistinguishable from wild-type enamel. Without WDR72, enamel mineral density increased early during the maturation stage but soon arrested. The null enamel layer was only a tenth as hard as wild-type enamel and under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 60 publications
7
49
0
Order By: Relevance
“…Therefore, the cellular infoldings of the ruffled ameloblasts are critical for NCKX4 to carry out its main function. These data are consistent with the phenotype reported in a mouse model with a mutation in WD repeat-containing protein 72 (Wdr72), in which NCKX4 also adopts an intracellular localization similar to what we have described here and the cyclic modulation from ruffled to smooth ameloblasts was abnormal (31).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the cellular infoldings of the ruffled ameloblasts are critical for NCKX4 to carry out its main function. These data are consistent with the phenotype reported in a mouse model with a mutation in WD repeat-containing protein 72 (Wdr72), in which NCKX4 also adopts an intracellular localization similar to what we have described here and the cyclic modulation from ruffled to smooth ameloblasts was abnormal (31).…”
Section: Discussionsupporting
confidence: 92%
“…This pattern suggests that the endocytosis mechanism, in the absence of KLK4, is still able to reabsorb much of the protein near the enamel surface, but the protein away from the surface is unable to work its way back to the cell for reabsorption. Interestingly, a pathological accumulation of enamel proteins also occurs in Wdr72 −/− mice, whose enamel shows more severe reductions in mineral density and hardness than those observed in Klk4 −/− mice [45,46]. WDR72 is an intracellular protein and defects in WDR72 contribute to the etiology of autosomal recessive amelogenesis imperfecta [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…WDR72 is an intracellular protein and defects in WDR72 contribute to the etiology of autosomal recessive amelogenesis imperfecta [47,48]. Identification of proteins that co-immunoprecipitated with WDR72 suggested that WDR72 is involved in endocytosis or vesicle trafficking [45,46]. These findings, and the discovery that Klk4 is a recent (evolutionary) addition to the process of enamel maturation, suggest that endocytosis is the primary mechanism for the removal of enamel matrix proteins and that secretion of the KLK4 enzyme is a later refinement that facilitates that process by degrading extracellular proteins and thereby allowing proteins in the deeper layers to more rapidly diffuse to the enamel surface and be reabsorbed by ameloblasts.…”
Section: Discussionmentioning
confidence: 99%
“…2015). Briefly, D14 first molars were incubated in 1 mL of 0.17 N HCl/0.95% formic acid for 2 h at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…2015). In brief, hemimandibles from 7‐week‐old mice were cleaned free of soft tissue and embedded in Epon resin following graded acetone dehydration.…”
Section: Methodsmentioning
confidence: 99%